(untitled) (Economics and region, 2022)
In the article the bases of organization of accounting of operations with securities of the enterprise are investigated. It is proved that the construction of a system of accounting for securities transactions at each particular enterprise should be subordinated to the main goal - to meet the information needs of users. The structure of such needs is quite complex, as it combines long-term and short-term interests of corporate relations subjects in the process of current and strategic activities. In this regard, the interests of users regarding securities transactions are grouped, which will increase the analytical value of information for the needs of category management in order to make effective management decisions. It is emphasized that the order on accounting policy in terms of securities transactions should be developed in such a way that it maximally meets the interests of the enterprise and leads to the formation of a scientifically based organizational and methodological structure of accounting for securities transactions at the request of information users. Such issues include: the procedure for creating and using the reserve for depreciation of securities; the procedure for accounting for expenses arising from transactions with securities; the procedure for increasing the registered (share) capital through the issue of securities and valuation of securities; list of working accounts, as well as the construction of analytical accounts for securities accounting; list and deadlines for submitting internal reporting on securities; disclosure of information on securities in accordance with the requirements of the National Securities and Stock Market Commission. The necessity of keeping internal management documentation on shareholders of a company is emphasized. Since the register of shareholders is the main document confirming the rights of legal entities and individuals to own shares, it is proposed to supplement it with such information as the date of purchase of shares, date of sale of shares, share in the registered (share) capital. Ultimately, this will affect the optimization of management decision-making taking into account specific types of securities, assessing the feasibility of issuing ordinary or preferred shares, determining the timing of dividend payments of business entities of various forms of ownership.